Pulmonary rehabilitation in patients with cystic fibrosis - (:unkn) unknown (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2022)
The respiratory secretions of patients with cystic fibrosis (CF) cause frequent pulmonary infections by thickening. These recurrent infections lead to lung damage and other pulmonary diseases. Pulmonary rehabilitation is descriptive in the management of CF and has an important role to clear the airways, to relieve shortness of breath and to increase chest expansion. Pulmonary rehabilitation of patients with CF includes individual-dependent techniques such as postural drainage, percussion and vibration

controlled breathing exercises such as autogenic drainage and active cycle of breathing technique

use of airway clearance devices such as the positive expiratory pressure device and devices that provide airway oscillation such as high frequency chest wall oscillation device. Exercises for poor posture and shortened accessory muscles of respiration should be integrated to all of these techniques. This article aims to define rehabilitation techniques for CF and to help the physicians to choose the suitable technique for the rehabilitation program.
Keywords: Cystic fibrosis; rehabilitation; pulmonary rehabilitation; CHEST-WALL OSCILLATION; AUTOGENIC DRAINAGE; AIRWAY CLEARANCE; POSTURAL DRAINAGE; PHYSICAL-ACTIVITY; EXERCISE; PHYSIOTHERAPY; CHILDREN; HEALTH